2009
DOI: 10.1292/jvms.71.1027
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Isobutyl-Paraben Exposure decreases the Plasma Corticosterone Level in Dams and Sensitivity to Estrogen in Female Offspring Rats

Abstract: ABSTRACT. Isobutyl-paraben (IBP), a widely used preservative in a variety of foods, shows high comparative binding affinity to estrogen receptors. Here, we examined the effects of maternal exposure of rats to IBP on plasma hormone concentrations and organ weights in dams, ratio of male pups, anogenital distance, organ weights and plasma hormone concentrations in offspring, puberty, estrous cycle and response of organ weight and plasma hormone concentrations to estrogen in adult female offspring, and reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
(46 reference statements)
0
14
0
1
Order By: Relevance
“…Previously, we showed that maternal exposure to IBP decreased uterine sensitivity to estrogen, which may be reflected in estrogen receptor (ER) expression in adult female offspring [19]. Similarly, previous works have shown that ER expression in animals treated with other estrogenic compounds is significantly lower than that in control animals [20,35].…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Previously, we showed that maternal exposure to IBP decreased uterine sensitivity to estrogen, which may be reflected in estrogen receptor (ER) expression in adult female offspring [19]. Similarly, previous works have shown that ER expression in animals treated with other estrogenic compounds is significantly lower than that in control animals [20,35].…”
mentioning
confidence: 73%
“…The removal of, or an increase in, maternal glucocorticoids leads to similar consequences: immobility in the forced swim test and hypothalamic glucocorticoid receptor expression in adult offspring [38]. Impairment in social recognition behavior may reflect a decrease in plasma corticosterone concentration in IBP-exposed dams [19]; however, further studies are, necessary to confirm this.…”
mentioning
confidence: 99%
See 3 more Smart Citations